Morpho-functional state of the liver and changes of blood biochemical parameters in rats exposed to lead sulfide nanoparticles in the remote terms of research. - S. T. Omelchuk; V. D. Aleksiychuk (Medičnì Perspektivi, 2014)
Recently, in the framework of technical progress a huge amount of nanoparticles arose, and unknowingly people come into contact with them as a result of industrial activities and in everyday life. Particularly noteworthy is the situation that concerns lead nanoparticles, because the possibility of its formation in the manufacturing process is sufficiently large, and the impact on the body is still poorly understood. The aim of our work was to determine the nature of morphological changes in the liver and dynamics of corresponding blood biochemical changes under exposure to lead sulfide nanoparticles of different sizes and lead nitrate in long-term administration of substances immediately and in long-term periods. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity in blood serum was studied by a colorimetric method with a set of «Phyllis Diagnostics» reagents. Histological sections of fixed liver preparations derived from routine experimental subjects served as materials for morphological studies. Studies have found that in long-term exposure to lead sulphide nanoparticles (groups 1 and 2) and ionic form of lead nitrate (group 3) activity of ALT and AST increases with the same levels of intensity. Decrease of activity of ALT and AST enzymes takes place in the post-exposure period. Morphological examinations of internal organs of experimental animals revealed presence of dystrophic changes in the liver parenchyma, reactive changes in hepatic stroma and vascular reactions, the intensity of which was more clearly marked in 60-fold administration of the test substances (12 weeks) and is expressed less in 60-fold administration of the same substances, taking into account the post-exposure period (18 weeks). The results will be taken into consideration at the subsequent stages of the study.